2020
DOI: 10.1108/jmlc-06-2020-0064
|View full text |Cite
|
Sign up to set email alerts
|

Perception versus reality: Iranian banks and international anti-money laundering expectations

Abstract: Purpose Iran has been ranked by the Basel Committee on Banking Supervision and the Financial Action Task Force (FATF) as one of the foremost countries in the world for money laundering. However, Iranian banks claim that they comply with international standards for reporting suspicious activity, risk management and training. This paper aims to investigate this dichotomy between perception and reality. Design/methodology/approach A Wolfsberg-style questionnaire was sent to partners in Iranian accounting firms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The auditor is also responsible for reviewing the actions of entities to obtain reasonable assurance of observing the money laundering laws, assessing their effectiveness, and obtaining management approval regarding observing the laundering regulations during the financial statements audit (Mohammadi et al, 2020). Additionally, auditors are expected to provide an independent appraisal of the effectiveness of AML systems in Iranian banks, offering their opinions on whether the entities have AML policies, practices, and procedures in place (Imeny et al, 2021b). The assessment confirmed that internal risk management systems in Iranian banks align satisfactorily with international AML expectations as outlined by the Wolfsberg criteria.…”
Section: Offering Expert Opinionsmentioning
confidence: 99%
“…The auditor is also responsible for reviewing the actions of entities to obtain reasonable assurance of observing the money laundering laws, assessing their effectiveness, and obtaining management approval regarding observing the laundering regulations during the financial statements audit (Mohammadi et al, 2020). Additionally, auditors are expected to provide an independent appraisal of the effectiveness of AML systems in Iranian banks, offering their opinions on whether the entities have AML policies, practices, and procedures in place (Imeny et al, 2021b). The assessment confirmed that internal risk management systems in Iranian banks align satisfactorily with international AML expectations as outlined by the Wolfsberg criteria.…”
Section: Offering Expert Opinionsmentioning
confidence: 99%
“…Moreover, the consistent and massive imposition of fines also arguably represents not achieving the intended outcome of deterring FIs from facilitating ML (Halliday et al , 2019). This divergence has contributed to the jurisdiction’s greylisting; it is attached to a political decision instead of risk management weaknesses in the financial sector (Imeny et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Schneider and Barone (2019) confirm the effectiveness of anti-money laundering regulations and state that these regulations have increased the cost of criminal organisations and consequently have been effective in reducing money laundering. Salehi et al (2019) and Molla Imeny et al (2020a, 2020b) examine the anti-money laundering structure of Iranian banks and state that Iranian banks have a proper anti-money laundering structure. But so far, the impact of intellectual and social capital on reducing money laundering and fraud in Iraq has not been studied.…”
Section: Introductionmentioning
confidence: 99%